METHOD OF PLANNING CONTROL AUTOMATED SYSTEM INTEGRITY IN THE OPERATION AND SUPPORT - Anton S. Lysunets; Boris A. Pozin (Открытое образование (Москва), 2016)
The article describes the problems of monitoring the integrity of sophisticated banking systems in the accompaniment. The understanding of the level of integrity of the automated system is described using estimates of the integrity level of the planning methodology of testing the automated banking system. Results of the article would be used in courses on Software Engineering and Banking Systems Automation.